PERANCANGAN SISTEM INFORMASI PEMBAYARAN SPP TERPADU MENGGUNAKAN MODEL PROTOTIPE - Imam Sutoyo (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2020)
SPP payment has become a main administrative activity in every educational institution, including Islamic Boarding School. SPP payment made only using manual procedures experience many obstacles. Therefore, a computer-based information system is needed to overcome these obstacles. This study aims to develop an SPP Payment System using the prototype model. The objective of this study is an Information Systems that can be applied practically in Islamic Boarding School to overcome obstacles in manual processing so as to increase the effectiveness and efficiency of the administration of SPP payments.